ANALISIS BEBAN KERJA DAN KEBUTUHAN ROOMBOY DI HOUSEKEEPING DEPARTMENT PREMIER BASKO HOTEL PADANG - Lisna, Yuke Permata; Chair, Ira Meirina; Kasmita, Kasmita (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2014)
This study aimed to determine how much workload given to roomboy and labor productivity in the Housekeeping Department roomboy Premier Basko Hotel Padang. The study consisted of two indicators of workload analysis and needs roomboy namely : the amount of work (number of rooms) and working time (per hour). This research is descriptive quantitative research. The population of this research is the data room occupancy on the number of uninhabited rooms, check out the number of rooms uninhabited rooms along with the percentage derived from the Housekeeping Department of Premier Basko Hotel Padang. The study concluded that the main tasks of this research are roomboy clean room uninhabited (occupied), check out the room, and the room is empty on one section (morning shift). The use of productive work time based roomboy given workload is over 360 minutes. Ideal number of requirements in Housekeeping Department roomboy Premier Basko Hotel Padang is 11 people in one section on the morning shift. Â Kata kunci : beban kerja, kebutuhan roomboy.